Higher Education in Three Dimensions A New Theoretical Frame of Understanding - Haukland, Linda Helén (Orkana Forlag AS, 2021)
'Higher Education in Three Dimensions. A New Theoretical Frame of Understanding' is a book of three parts. Part I is an institutional analysis of the change dynamics of the Norwegian higher education field between 1965 and 2011, and the foundation of the University of Nordland, now Nord University. The analysis examines the foundation of Nordland Regional University College, the development of the national university and university college sectors and the regional university colleges in Bodø up to the founding of the University of Nordland. Part II presents a new theoretical frame of understanding for analysing development driven by these tensions and by other factors. It also questions the two-dimensional understanding of terms such as autonomy and academic drift, and suggests society is included as a stronger third dimension in the analysis of higher education. Part III concludes that a three-dimensional framework of understanding highlights new key themes, issues and dilemmas in the field of higher education. It is therefore both fruitful and needed as it will allow a greater depth of understanding, comparative analysis, and the uncovering of the dilemmas at stake.